Cuticle lipids on heteromorphic leaves of Populus euphratica Oliv. growing in riparian habitats differing in available soil moisture. Issue 3 (8th June 2016) - Xu, Xiaojing; Xiao, Lei; Feng, Jinchao; Chen, Ningmei; Chen, Yue; Song, Buerbatu; Xue, Kun; Shi, Sha; Zhou, Yijun; Jenks, Matthew A.
Abstract : Populus euphratica is an important native tree found in arid regions from North Africa and South Europe to China, and is known to tolerate many forms of environmental stress, including drought. We describe cuticle waxes, cutin and cuticle permeability for the heteromorphic leaves of P. euphratica growing in two riparian habitats that differ in available soil moisture. Scanning electron microscopy revealed variation in epicuticular wax crystallization associated with leaf type and site. P. euphratica leaves are dominated by cuticular wax alkanes, primary‐alcohols and fatty acids. The major cutin monomers were 10, 16‐diOH C16 :0 acids. Broad‐ovate leaves (associated with adult phase growth) produced 1.3‐ and 1.6‐fold more waxes, and 2.1‐ and 0.9‐fold more cutin monomers, than lanceolate leaves (associated with juvenile phase growth) at the wetter site and drier site, respectively. The alkane‐synthesis‐associated ECERIFERUM1 ( CER1 ), as well as ABC transporter‐ and elongase‐associated genes, were expressed at much higher levels at the drier than wetter sites, indicating their potential function in elevating leaf cuticle lipids in the dry site conditions. Higher cuticle lipid amounts were closely associated with lower cuticle permeability (both chlorophyll efflux and water loss). Our results implicate cuticle lipids as among the xeromorphic traits associated with P. euphratica adult‐phase broad‐ovate leaves. Results here provide useful information for protecting natural populations of P. euphratica and their associated ecosystems, and shed new light on the functional interaction of cuticle and leaf heterophylly in adaptation to more arid, limited‐moisture environments.